Evaluating of the Implementing of the 12-Years Compulsory Learning Program in Southeast Sulawesi - Falihin, Falihin; Sugiarto, Sugiarto; Suryadi, Suryadi (Jurnal Paedagogy, 2023)
This research aims to analyze the results of implementing the 12-year compulsory education program using the CIPP model in Southeast Sulawesi study using a qualitative approach with a CIPP evaluation method (context, input, process, and product). The research was conducted in the Province of Southeast Sulawesi, specifically at the Department of Education and Culture of Southeast Sulawesi. The participants involved were the head of the education and culture office at the Southeast Sulawesi Province Education and Culture Office and the head of the section responsible for managing elementary to high school education. School principals and teachers from elementary school, junior high school and senior high school are 50 people. Data collection techniques used observation, interviews, and documentation studies. Data analysis in this study consisted of three stages, namely 1) data reduction, 2) data presentation, and 3) conclusion. The study results showed that the 12-year compulsory education program had been implemented correctly. The context aspect had been carried out by the laws and regulations set by the government. The input aspect showed that program planning was adjusted to legality and field needs. However, the resources for education personnel were still lacking, and the government in Southeast Sulawesi government had appointed honorary teachers and provided various training to improve their competence. Whereas in the process aspect, it was shown in the lack of learning facilities and infrastructure, which still needs to be completed by developments in global needs so that graduates can be qualified, and in the product aspect, it has been shown by the achievement of pure enrollment rates and gross enrollment rates that exceed the initial target. So, this research has implications for the awareness of all parties involved in the implementation of education that the responsibility for the success of this compulsory education program requires cooperation.